Delayed Relapse of Paracoccidioidomycosis in the Central Nervous System: A Case Report. (2nd March 2020) - Rahman, Rifat; Davies, Leela; Mohareb, Amir M; Peçanha-Pietrobom, Paula M; Patel, Nirav J; Solomon, Isaac H; Meredith, David M; Tsai, Harrison K; Guenette, Jeffrey P; Bhattacharyya, Shamik; Urday, Sebastian; Velásquez, Gustavo E
Abstract: Paracoccidioidomycosis is a dimorphic fungal infection endemic in Latin America. We report a patient with a history of pulmonary paracoccidioidomycosis who presented with relapsed disease in the central nervous system 4 years after initial treatment. We review current treatment strategies for paracoccidioidomycosis and neuroparacoccidioidomycosis.